The symbolic violence of setting: A Bourdieusian analysis of mixed methods data on secondary students' views about setting. (15th January 2018) - Archer, Louise; Francis, Becky; Miller, Sarah; Taylor, Becky; Tereshchenko, Antonina; Mazenod, Anna; Pepper, David; Travers, Mary‐Claire
Abstract : 'Setting' is a widespread practice in the UK, despite little evidence of its efficacy and substantial evidence of its detrimental impact on those allocated to the lowest sets. Taking a Bourdieusian approach, we propose that setting can be understood as a practice through which the social and cultural reproduction of dominant power relations is enacted within schools. Drawing on survey data from 12, 178 Year 7 (age 11/12) students and discussion groups and individual interviews with 33 students, conducted as part of a wider project on secondary school grouping practices, we examine the views of students who experience setting, exploring the extent to which the legitimacy of the practice is accepted or challenged, focusing on students' negative views about setting. Analyses show that privileged students (White, middle class) were most likely to be in top sets whereas working‐class and Black students were more likely to be in bottom sets. Students in the lowest sets (and boys, Black students and those in receipt of free school meals) were the most likely to express negative views of setting and to question the legitimacy and 'fairness' of setting as a practice, whereas top‐set students defended the legitimacy of setting and set allocations as 'natural' and 'deserved'. This paper argues that setting is incompatible with social justice approaches to education and calls for the foregrounding of the views of those who are disadvantaged by the practice as a tool for challenging the doxa of setting.